CONTRIBUTIONS OF THE MARXIST APPROACH TO LABORFORCE MOBILITY TO THE STUDY OF THE HISTORICAL GEOGRAPHY OF MIGRATION IN BRAZIL - Ismael, Vinicius de Paula [UNESP]; Nascimento, Ramon Spironello do [UNESP]; Rosalin, Joao Paulo [UNESP] (Univ Federal Mato Grosso, 2021)
The present work aims to bring an analysis of the historical geography of migration in Brazil through the concept of laborforce mobility developed by Gaudemar (1977). Thus, our analysis is based on the changes that the spatial mobilization of labor forces underwent (through internal and international migrations) throughout the historical development of capitalism in Brazil, identifying three historical periods in which mobilization is expressed in different ways: a first period comprising the end of the 19th century (with the adoption of free work) and the 1930s, with the predominance of international migrations; a second marked by the growth of internal migrations (from the 1930s to the mid-1970s); and a third period corresponding to the global capitalist expansion and the complexification of migrations.
Keywords: Migrations; Labor mobility; historical geography